Conducting Sensitive Interviews Online - Kähäri, Outi (Wiley [Commercial Publisher], 2025)
We explore the role of embodied messages for the interaction orderwhen conducting sensitive biographical research online. Our analysisindicates that mediated situations take shape continuously and areextremely open to different kinds of interaction orderings, includ-ing disruptions. Interaction in online interviews is influenced byincreased fluidity and intensity caused by the synthetic situation. Forthe researcher, this results in extra effort in restructuring the mainactivity and re-establishing the expressive order. Moreover, the inabilityto be physically present in affective interview situations created virtualprivate mental spaces where interaction of intense emotions was partlyrestricted.